Intramuscular Cavernous Hemangioma of Medial Rectus Muscle in Paediatric Age Group. (13th March 2017) - Mehta, Anuj; Butola, Shalini; Naik, Mayuresh; Abrol, Sangeeta; Kumari, Anju
Abstract : An 11-year-old male child presented with a mass on the nasal aspect of the right eye that has been there for the last 2 years. Extraocular movements were decreased in the right eye on levoversion, levoelevation, and levodepression. Local examination revealed a bluish mass with irregular surface and ill-defined margins located in the medial rectus muscle. The mass was 10 × 20 mm in size, firm, nodular, nontender, nonpulsatile, noncompressible, and nonreducible. MRI of the orbit revealed a well-defined mass of approximately 23 × 13 mm along the medial rectus (MR) muscle. It was hyperintense on T2 W images with very minimal contrast enhancement. A provisional diagnosis of hemangioma or lymphangioma with intralesional haemorrhage was made. During surgical excision, the mass was found to be encapsulated by MR fibres. The MR fibres were separated, and the mass measuring 20 × 8 × 6.5 mm was removed and sent for histopathology. The histopathological examination revealed an intramuscular cavernous hemangioma.